A Rare presentation of neurobrucellosis in a child with Recurrent transient ischemic attacks and pseudotumor cerebri (A case report and review of literature) - AKHONDIAN*, Javad; ASHRAFZADEH, Farah; BEIRAGHI TOOSI, Mehran; HASHEMI, Nargess (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Akhondian J, Ashrafzadeh F, Beiraghi Toosi M, Hashemi N. A Rare Presentation of Neurobrucellosis in A Child with Recurrent Transient Ischemic Attacks and Pseudotumor Cerebri (A Case Report and Review of Literature). Iran J Child Neurol. 2014 Spring; 8(2):65-69. Brucellosis is a multi-system infectious disease that presents with various manifestations and complications. Neurobrucellosis is an uncommon but serious presentation of brucellosis that can be seen in all stages of the disease. High index of suspicion, especially in endemic areas is essential to prevent morbidity from this disease. The case was an 11- year -old female patient who was admitted with a severe headache that was worsening over a period of 2 months. The day after each attack, she experienced transient right hemiparesia that was lasting less than one hour (TIA) as well as blurred vision and bilateral papilledema. Laboratory findings revealed serum agglutination Wright test positive at 1/320 and 2ME test positive at 1/160. A lumbar puncture showed a clear CSF with increased opening pressure (32 cmH2O), CSF examination was within normal range (pseudotumor cerebri).To our knowledge, there has been no report for recurrent TIA in pediatric neurobrucellosis in the base of pseudotumor cerebri. In endemic areas like Iran, unexplained neurological signs or symptoms should be evaluated for brucellosis. References 1. Pappas G, Akritidis N, Bosilkovski M, Tsianos E. Brucellosis. N Engl J Med 2005; 352 2325-2336. 2. Young EJ, Mandel GL, Bennett JE, et al. Principles and practice of infectious diseases. Philadelphia: Churchill Livingstone; 2002; Pp:23 86-93. 3. Gul HC, Erdem H, Bek S. Overview of neurobrucellosis: a pooled analysis of 187 cases. Int J Infect Dis. 2009;13(6):339-343. 4. McLean DR, Russell N, Khan MY. Neurobrucellosis: Clinical and therapeutic features. Clin Infect Dis. 1992; 15:582-90. 5. Young EJ, Douglas M. Brucella species. Bennett’s principles and practice of infectious diseases. 6th ed. Churchill Livingstone Co. 2005; 6: 2669-73. 6. Fatima ZO, Samer Z, Ropert A. Neurobrucellosis in children. Developmental Medicine & Child Neurol.1997;39:762-765. 7. Habib YKR, AL – Najdi AKN, Sadek SAH. Paediatric Neurobrucellosis: Case Report and Literature Review. J Infection 1998; 37:59-62. 8. Bucher A, Gaustad P, Pape E. Chronic neurobrucellosis due to Brucella melitensis. Scand J Infect Dis 1990; 22:223-6. 9. Al Deeb SM, Yaqub BA, Sharif HS, et al. Neurobrucellosis: clinical characteristics, diagnosis, and outcome. Neurology 1989; 39:498-501. 10. Shakir RA, Al-Din ASN, Araj GF, et al. Clinical categories of neurobrucellosis; a report on 19 cases. Brain. 1987;110: 213-223. 11.Haji-Abdolbagi M, Rasooli-Nejad M, Jafari S, et al. Clinical and laboratory findings in neurobrucellosis: Review of 31 Cases. Arch Iranian Med 2008; 11 (1): 21-25. 12. Ranjbar M, Rezaiee AA, Hashemi SH, et al. Neurobrucellosis: report of a rare disease in 20 Iranian patients referred to a tertiary hospital. Eastern Mediterranean Health Journal. 2009; 15(1): 143-148. 13. Sturniolo G, Mondello P, Bruno S, et al. Neurobrucellosis associated with syndrome of inappropriate antidiuretic hormone with resultant diabetes insipidus and hypothyroidism. Journal of clinical microbiology. 2010; 48(10): 3806-3809. 14. Trifiletti RR, Restivo DA, Pavone P, et al. Diabetes insipidus in neurobrucellosis. Clin Neurol Neurosurg. 2000; 102: 163- 165. 15. Zaidan R, Al Tahan AR. Cerebral venous thrombosis: a new manifestation of neurobrucellosis. Clin Infect Dis.1999; 28: 399 - 400. 16. Namiduru M, Karaoglan I, Yilmaz M. Guillain-Barre syndrome associated with acute neurobrucellosis. Int J Clin Pract. 2003; 57: 919 - 920. 17. Tuncer-Ertem G, Tülek N, Yetkin MA. Case report: subdural hemorrhage in neurobrucellosis. Mikrobiyol Bul. 2004; 38: 253 - 256. 18. Tena D, Gonzáles-Praetorius A, López- Alonso A, Peña JL, Pérez-Pomata MT, Bisquert J. Acute meningitis due to Brucella spp. Eur J Pediatr 2006; 165:726-727. 19. Salih M A, Abdel G M. Abdel G, et al. Infectious and in ammatory disorders of the circulatory system as risk factors for stroke in Saudi children. Saudi Med J. 2006;27: 41-52. 20. Sayyahfar Sh, Karimi A, Fahimzad A , et al. Rare presentation of neurobrucellosis. Pak J Med Sci. 2008; 24(3): 464-467. 21. Hernandez MA, Anciones B, Frank A, et al. Neurobrucellosis and cerebral vasculitis. Neurologia 1988; 3:241-243. 22. Adaletli I, Albayram S, Gurses B, et al. Vasculopathic changes in the cerebral arterial system with neurobrucellosis. Am J Neuroradiol 2006; 27:384-386. 23. Bingöl A, Togay-Isıkay C. Neurobrucellosis as an exceptional cause of transient ischemic attacks. Eur J Neurol 2006; 13:544-548. 24.Elrazak MA. Brucella optic neuritis. Arch Intern Med 1991;151:776-8. 25. Karakurum G B, Yerdelen D, Karatas M, et al. Abducens nerve palsy and optic neuritis as initial manifestation in brucellosis. Scand J Infect Dis 2006; 38:721-5. 26. Karapinar B, Yilmaz D, Vardar F, et al. Unusual presentation of brucellosis in a child: Acute blindness. Acta Paediatrica. 2005;94:378-80. 27. Marques R, Martins C, Machado I, et al. Unilateral optic neuritis as a presentation of neurobrucellosis. Pediatric Reports. 2011; 3(11): 36-38. 28. Tali ET, Keskin T, Oznur II, et al. MRI of brucella polyneuritis in a child. Neuroradiology. 1996; 38(1): 190-2. 29. Yilmaz M, Ozaras R, Mert A, et al. Abducent nerve palsy during treatment of brucellosis. Clin Neurol Neurosurg 2003; 105:218-20. 30. Balcer LJ. Optic neuritis. N Engl J Med 2006; 354:1273-1280. 31. Dirge KB. Idiopathic intracranial hypertension. BMJ 2010; 341:109-110. 32. Emadoleslamia M, Mahmoudianb T. A case of pseudotumor cerebri and brucellosis. Pediatr Infec Dis J .2007;2: 251-253. 33. Yasar anlar F, yalcin S, Secmeer G. Persistant hypoglycorrhachia in neurobrucellosis. pediatr infec j. 1994;13(8):747-8. 34. Erdem H, Ulu-Kilic A, Kilic S, et al. Efficacy and tolerability of antibiotic combinations in neurobrucellosis: results of the Istanbul study. Antimicrob Agents Chemother. 2012; 56(3):1523-8.